Noncovalent Polymerization‐Activated Ultrastrong Near‐Infrared Room‐Temperature Phosphorescence Energy Transfer Assembly in Aqueous Solution - Dai, Xian‐Yin; Huo, Man; Dong, Xiaoyun; Hu, Yu‐Yang; Liu, Yu (Advanced materials (Weinheim), 2022)
Noncovalent macrocycle‐confined supramolecular purely organic room‐temperature phosphorescence (RTP) is a current research hotspot. Herein, a high‐efficiency noncovalent polymerization‐activated near‐infrared (NIR)‐emissive RTP‐harvesting system in aqueous solution based on the stepwise confinement of cucurbit[7]uril (CB[7]) and β‐cyclodextrin‐grafted hyaluronic acid (HACD), is reported. Compared with the dodecyl‐chain‐bridged 6‐bromoisoquinoline derivative (G), the dumbbell‐shaped assembly G⊂CB[7] presents an appeared complexation‐induced RTP signal at 540 nm via the first confinement of CB[7]. Subsequently, benefitting from the stepwise confinement encapsulation of the β‐cyclodextrin cavity, the subsequent noncovalent polymerization of the binary G⊂CB[7] assembly enabled by HACD can contribute to the further‐enhanced RTP emission intensity approximately eight times in addition to an increased lifetime from 59.0 µs to 0.581 ms. Moreover, upon doping a small amount of two types of organic dyes, Nile blue or tetrakis(4‐sulfophenyl)porphyrin as an acceptor into the supramolecular confinement assembly G⊂CB[7] @ HACD, efficient RTP energy transfer occurs accompanied by a long‐lived NIR‐emitting performance (680 and 710 nm) with a high donor/acceptor ratio. Intriguingly, the prepared RTP‐harvesting system is successfully applied for targeted NIR imaging of living tumor cells by utilizing the targeting ability of hyaluronic acid, which provides a new strategy to create advanced water‐soluble NIR phosphorescent materials. A highly efficient noncovalent polymerization‐activated phosphorescence‐harvesting system is successfully constructed in aqueous solution based on the stepwise confinement of cucurbit[7]uril and β‐cyclodextrin‐grafted hyaluronic acid, which shows high phosphorescence energy transfer efficiency accompanied by a long‐lived near‐infrared (NIR) emitting performance, and is ultimately applied for NIR targeted imaging of cancer cells.